Oxygen Extraction Based on Inspiratory and Expiratory Gas Analysis Identifies Ventilatory Inefficiency in Chronic Obstructive Pulmonary Disease - Miki, Keisuke; Tsujino, Kazuyuki; Maekura, Ryoji; Matsuki, Takanori; Miki, Mari; Hashimoto, Hisako; Kagawa, Hiroyuki; Kawasaki, Takahiro; Kuge, Tomoki; Kida, Hiroshi (Frontiers in Physiology, 2021)
Aims: In contrast to cardiovascular disease, low rather than high ventilatory inefficiency, evaluated by the minute ventilation-carbon dioxide output (V’E-V’CO2)-slope, has been recognized as being related to greater disease severity in chronic obstructive pulmonary disease (COPD). To better care for patients with cardiopulmonary disease, understanding the physiological correlation between ventilatory inefficiency and exercise limitation is necessary, but remains inadequate. Given that oxygen uptake (V’O2) evaluated by cardiopulmonary exercise testing (CPET) depends on both the ventilatory capability and oxygen extraction, i.e., the difference between inspiratory and expiratory oxygen concentration (delta FO2), the aim of this study was to investigate the correlations between V’E-V’CO2-slope and the delta FO2 during exercise and their physiological implications in patients with COPD. Methods: A total of 156 COPD patients (mean age, 70.9 ± 7.2 years) with Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages I–IV and 16 controls underwent CPET with blood gas analysis. Results: With the progression of COPD, mechanical ventilatory constraints together with a slower respiratory frequency led to exertional respiratory acidosis. In GOLD IV cases, 1) decrease in the dependence of reduced peak V’O2 on V’E led to an increase in its dependence on peak delta FO2 during exercise; and 2) the delta FO2-V’CO2-slope became steeper, correlating with the severity of exertional respiratory acidosis (r=0.6359, p<0.0001). No significant differences in peak exercise delta FO2 or V’E-V’CO2-slope were observed among the various GOLD stages. In all subjects, including controls, peak exercise delta FO2 had the strongest correlation with the V’E-V’CO2-slope (r=-0.8835, p<0.0001) and correlated well with body mass index (r=0.3871, p<0.0001), although it did not correlate with the heart rate-V’CO2-relationship and V’E. Conclusions: Ventilatory efficiency related to CO2 clearance might depend on exertional oxygen extraction in the body. Measuring delta FO2 might be a key component for identifying ventilatory inefficiency and oxygen availability. Increasing delta FO2 would help to improve ventilatory inefficiency and exercise tolerance separately from cardiac and ventilatory capability in COPD patients.